2022
DOI: 10.1016/j.ekir.2021.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Urine Single-Cell RNA Sequencing in Focal Segmental Glomerulosclerosis Reveals Inflammatory Signatures

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 59 publications
0
45
0
Order By: Relevance
“…Next, we wanted to know whether any of these TEC phenotypes are specific for the damage introduced by AKI: We compared our data with recently published urinary scRNAseq data of chronic glomerular diseases DN (18) and FSGS (19) (Suppl. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, we wanted to know whether any of these TEC phenotypes are specific for the damage introduced by AKI: We compared our data with recently published urinary scRNAseq data of chronic glomerular diseases DN (18) and FSGS (19) (Suppl. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Together with data from DN (18) and FSGS (19) patients, urinary scRNAseq has now been tested in three credible cohorts across different diseases. These studies revealed a high variability of the viable cell count across samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 scRNA-seq has also been used to characterize the urinary sediment of patients hospitalized with COVID-19 7 and to define the cellular profile of healthy urine. 8 In this issue of KI Reports, Latt et al 9 used a pilot approach to test the utility scRNA-seq in characterizing the urinary transcriptomic profile of 12 subjects with FSGS. The findings reveal the presence of immune cells, podocytes, myofibroblasts, and tubular cells with distinct expression profiles.…”
Section: See Translational Research On Page 289mentioning
confidence: 99%